Near-Earth heliospheric magnetic field intensity since 1750: 2. Cosmogenic radionuclide reconstructions - Owens, M. J. (2017)
This is Part 2 of a study of the near-Earth heliospheric magnetic field strength, B, since 1750. Part 1 produced composite estimates of B from geomagnetic and sunspot data over the period 1750-2013. Sunspot-based reconstructions can be extended back to 1610, but the paleocosmic ray (PCR) record is the only data set capable of providing a record of solar activity on millennial timescales. The process for converting Be-10 concentrations measured in ice cores to B is more complex than with geomagnetic and sunspot data, and the uncertainties in B derived from cosmogenic nuclides (similar to 20% for any individual year) are much larger. Within this level of uncertainty, we find reasonable overall agreement between PCR-based B and the geomagnetic- and sunspot number-based series. This agreement was enhanced by excising low values in PCR-based B attributed to high-energy solar proton events. Other discordant intervals, with as yet unspecified causes remain included in our analysis. Comparison of 3year averages centered on sunspot minimum yields reasonable agreement between the three estimates, providing a means to investigate the long-term changes in the heliospheric magnetic field into the past even without a means to remove solar proton events from the records.